The Construction of „Male Capability“ and „Female Inability” to assume Guardianship of Children in the Austrian “Allgemeines Bürgerliches Gesetz-buch” (ABGB) in the 19th Century” - Forster, Ellinor (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
When the ABGB was published in 1811 it contained the provision that women were not allowed to take over guardianship of children except mothers or grandmothers.1 If the father had not appointed a guardian in his last will, first the paternal grandfather, then the mother and after the paternal grandmother all other male relatives were considered as guar-dians.2 In contrast to male guardians the mother and grandmother had the possibility to refuse. This can be seen as a reflection of old female “protective” measures to pretend them from acting against their advantage. It fits into the picture that whenever mothers or grandmothers took over guardianship they needed a so-called Mitvormund (co-guardian).3 The argumentation for prohibiting women other than mothers and grandmothers to take over guardianship was that they were thought not to have enough knowledge of business affairs. Franz von Zeiller, the person mainly responsible for the final formulation of the civil code, wrote in his law commentary: „Der Grund der Vorschrift ist offenbar, weil es diesen Personen gewöhnlich … an den nothwendigen Kenntnissen … mangelt.“4 He saw the care of their own children as the mothers’ and grandmothers’ primary duty, but a co-guardian was needed, „um das vorzüglich in Rechtsgeschäften minder erfahrene Geschlecht in Führung derselben zu unterstützen.“5 Both the father and the mother had the right to propose a co-guardian, but the court was not bound by this proposal. Before I interpret these assumptions I want to take a look on the process leading up to this provision because looking at the history of the work on the codification, another outcome was also possible. After that I trace the development throughout the 19th century, take a look at the efforts of the women’s movement at the turn of the century and finally sketch the change of law right before the outbreak of World War I in 1914. At the center of my considerations are always the arguments used for explaining the different prohibitions or demands because they throw a light on the representations of gender roles among different social groups and during different periods.